Mechanisms of Severe Mortality-Associated Bacterial Co-infections Following Influenza Virus Infection - Jia, Leili; Xie, Jing; Zhao, Jiangyun; Cao, Dekang; Liang, Yuan; Hou, Xuexin; Wang, Ligui; Li, Zhenjun (Frontiers in Cellular and Infection Microbiology, 2017)
Influenza virus infection remains one of the largest disease burdens on humans. Influenza-associated bacterial co-infections contribute to severe disease and mortality during pandemic and seasonal influenza episodes. The mechanisms of severe morbidity following influenza-bacteria co-infections mainly include failure of an antibacterial immune response and pathogen synergy. Moreover, failure to resume function and tolerance might be one of the main reasons for excessive mortality. In this review, recent advances in the study of mechanisms of severe disease, caused by bacterial co-infections following influenza virus pathogenesis, are summarized. Therefore, understanding the synergy between viruses and bacteria will facilitate the design of novel therapeutic approaches to prevent mortality associated with bacterial co-infections.